Analysis of School-Based Management and Principal Leadership in Improving Teacher Performance - Sundari, Sundari; Suwito, Suwito; Wibowo, Eri (Journal of Innovation in Teaching and Instructional Media, 2023)
This article discusses the general problem of low teacher performance in many schools in Indonesia, which can be seen from the school's consistently low qualitative average scores. The main goal of this article is to evaluate potential solutions to improve teacher effectiveness. The focus centers on two important aspects: the implementation of School Based Management (SBM) and the leadership style of the school principal. Identified challenges hindering teacher performance, including poor adaptation, lack of communication skills, and lack of openness to diverse opinions, will be examined. By using a descriptive analysis method with a qualitative approach, the author provides recommendations. The results of this article involve the implementation of a comprehensive principal leadership model that integrates visionary, democratic, and instructional elements, emphasizing support, collaboration, and commitment to ongoing professional development and motivation. The proposed model is expected to significantly improve teacher performance in schools in Indonesia.